2021
DOI: 10.1136/bmjopen-2020-043166
|View full text |Cite
|
Sign up to set email alerts
|

Examining chronic inflammatory markers on blood pressure measures in the presence of vitamin D insufficiency among indigenous cree adults: results from the cross-sectional Multi-Community Environment-and-Health Study inEeyou Istchee, Quebec, Canada

Abstract: ObjectiveHigh blood pressure (BP) is a risk factor for cardiovascular disease. Examining the role of inflammatory mediators on BP is important since vitamin D (VD) is a modifiable risk factor, which possibly modulates inflammatory cytokines. This study simulated what are known as average ‘controlled direct effects (CDE)’ of inflammatory markers, C reactive protein (CRP), tumour necrosis factor-α (TNF-α), and interlukin-6 (IL-6) on continuous BP measures, while fixing VD, an intermediate variable to specific le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
1
1
Order By: Relevance
“…49 Supplementation of T2DM patients with 25[OH]D was shown to cause an improvement of their inflammatory status. 50 Similarly, in hypertensive patients, a correlation was established between 25[OH]D insufficiency and SBP in hypertensive patients, 51 which was contrary to the results of the current study where there was no correlation of the level of 25[OH]D with TNF-α in either T2DM or hypertensive patients. An explanation for such discrepancy may be due to the increment of GSH seen in the present study that might blunt the oxidative stress, which might be a main determinant factor of induction of inflammatory pathway.…”
Section: Discussioncontrasting
confidence: 99%
“…49 Supplementation of T2DM patients with 25[OH]D was shown to cause an improvement of their inflammatory status. 50 Similarly, in hypertensive patients, a correlation was established between 25[OH]D insufficiency and SBP in hypertensive patients, 51 which was contrary to the results of the current study where there was no correlation of the level of 25[OH]D with TNF-α in either T2DM or hypertensive patients. An explanation for such discrepancy may be due to the increment of GSH seen in the present study that might blunt the oxidative stress, which might be a main determinant factor of induction of inflammatory pathway.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have shown that vitamin D de ciency is a global public health problem and that epidemics often have a more severe impact on the elderly and those with complications such as obesity, diabetes, hypertension, respiratory disease, recurrent infections, immune de ciency, and malignant tumors [12]. Low vitamin D levels are associated with an increased risk of obesity and exacerbated in ammation for health bene ts [13,14]. Adequate vitamin D may prevent obesity and obesity-related diseases by inducing Ca 2+− mediated adipocyte apoptosis through the anti-obesity mechanism of 1,25 (OH) D2D3 [15].…”
Section: Discussionmentioning
confidence: 99%